2012
DOI: 10.1140/epje/i2012-12110-2
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic models for DNA stretching under force: New results and comparison with experiments

Abstract: Single molecule experiments on double stranded B-DNA stretching have revealed one or two structural transitions, when increasing the external force. They are characterized by a sudden increase of DNA contour length and a decrease of the bending rigidity. The nature and the critical forces of these transitions depend on DNA base sequence, loading rate, salt conditions and temperature. It has been proposed that the first transition, at forces of 60-80 pN, is a transition from B to S-DNA, viewed as a stretched du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 64 publications
3
21
0
Order By: Relevance
“…However this type of approach remains valid for very high stretching of ssDNA [75] provided that both the discrete nature of the chain is taken into account [98] and non-linear stretching terms are included [74]. Fits of force-extension curves of ssDNA up to 1200 pN, as shown in Figure 3a, have been nicely fitted using the modified formula that includes both terms [27]: [74]. The fit leads to the bending modulus value κ(ssDNA) = 1.5 k B T and an effective monomer length a = 0.20 nm (see Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However this type of approach remains valid for very high stretching of ssDNA [75] provided that both the discrete nature of the chain is taken into account [98] and non-linear stretching terms are included [74]. Fits of force-extension curves of ssDNA up to 1200 pN, as shown in Figure 3a, have been nicely fitted using the modified formula that includes both terms [27]: [74]. The fit leads to the bending modulus value κ(ssDNA) = 1.5 k B T and an effective monomer length a = 0.20 nm (see Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has witnessed their rapid development, and the reader can for example refer to Refs. [26][27][28][29][30][31][32][33] for further detail. When the connection with TPM experiments is meaningful, we shall discuss some works dealing with force and torque experiments in the present Review.…”
Section: Introductionmentioning
confidence: 99%
“…Er -k\(r -ro)2, Eg = £2 (Co + C\ cosO + C2cos20), Ci = 1 2 , Ci = -4 C 2cos0o, Co = C2(2cos20o + 1), 4 su r 0 (13) Here, ku k2, k3 , and k4 are force constants, 0o is the natural bond angle, D is the van der Waals well depth, r* is the van der Waals length, <? ; is the net charge of an atom, g is the dielectric constant, and r,y is the distance between two atoms.…”
Section: Molecular Mechanics Molecular Mechanics Simulations Have Bementioning
confidence: 99%
“…However, to develop computing devices using DNA, it is necessary to know structural deformation and stability properties [7] under a wide range of mechanical and thermal conditions. Computational methods have been therefore developed for the mechanical analy sis of DNA [11][12][13] and other biological molecules. Over the past two decades, it has been possible to conduct single molecule experiments and observe de formation patterns under various loading conditions [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…13,[17][18][19] Great efforts have been made to study the behaviors of single DNA molecule under stretching. [20][21][22][23] However, little is known about elastic behaviors of DNA during their unbinding processes because of the complexity of the DNA binding structures and biophysical properties. 24 In this study, we revealed the single molecule elastic properties from the experimentally measured AFM data, and developed a relatively simple and practical elasticity model to quantitatively explain the elastic behaviors of ssDNA during the single molecule binding/unbinding reaction.…”
mentioning
confidence: 99%